O protagonismo de mulheres sateré-mawé no movimento indígena: a experiência organizativa da Associação Watyamã em Barreirinha/AM - Batista, Ingrid Noronha Viana (Brasil, 2025)
This article comes from the Specialization Course in “State, Work and Public Policies”, at the Federal University of Amazonas (UFAM), at the Institute of Social Sciences, Education and Animal Science (ICSEZ). With the title “The Protagonism of Sateré-Mawé Women in the Indigenous Movement: The Organizational Experience of the Watyamã Association in Barreirinha/AM”. With the aim of analyzing the participation of Sateré-Mawé women in the indigenous social movement in the municipality of Barreirinha, focusing on the Watyamã Association. Seeking to understand how they join social movements and the functioning of their organizational structure and what their contributions are to strengthening struggles to guarantee their social rights. This is an exploratory research, qualitative and documentary in nature. Having Verdum (2008) as a theoretical basis, which emphasizes on indigenous women in contemporary times. Pointing out new agendas and concerns, enriching the debate and bringing women increasingly into the collective space.